Iberian Peninsula cowpea diversity: chloroplast, microsatellite and morpho-agronomic variability. Issue 2 (28th November 2020) - Monteiro, Eliana; Castro, Isaura; Carvalho, Márcia; Martín, Juan Pedro; Rosa, Eduardo; Carnide, Valdemar
Abstract : Cowpea ( Vigna unguiculata (L.) Walp.) is an important legume crop in Southern Europe and a valuable source of proteins, minerals, and vitamins. Moreover, cowpea has additional interest stemming from drought tolerance and high biological nitrogen fixation. In this research, the genetic diversity of cowpea landraces from Southern European countries was evaluated using molecular and morpho-agronomical approaches, with the objective of enhancing legumes diversity grown through sustainable cropping. A set of 10 chloroplast microsatellite primer pairs (cpSSRs) was used to evaluate genetic diversity and phylogenetic relationships among 113 Vigna accessions including Vigna unguiculata subsp. unguiculata, subsp. alba, subsp. pubescens, subsp . tenuis and var. spontanea and accessions from other Vigna species, as V. mungo, V. radiata and V. racemosa . This set of primers successfully established ten haplotypes, with the most frequent being shared by the V . unguiculata subsp. unguiculata cultigroups unguiculata and sesquipedalis and var. spontanea. Eight loci were polymorphic; nevertheless, a low level of polymorphism was verified within the cultivated cowpeas. Additionally, 10 agronomic traits were evaluated on cowpea landraces of the cultigroup unguiculata, mainly from Portugal. PCA clustered the landraces into three main groups, each one containing Portuguese landraces. Total seed weight per plant revealed the highest coefficient of variation, and 100 seed weight the highest heritability. The performed study shows the wide agro-morphological diversity still existing in cowpea in Iberian Peninsula and other Southern European countries, despite the low polymorphism detected in its chloroplast genome. The high variability detected in the collection of cowpea analysed and the sharing of haplotypes by cultivated and wild material is of great importance for breeding programs of this species.